Video on dry land farming in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
two part video film on dryland farming in Africa, which has been co-produced by ICRISAT (International Crops Research Institute for the Semi-Arid Tropics) and the Open University of the United Kingdom